A review of threat modelling approaches for APT-style attacks. Issue 1 (January 2021) - Tatam, Matt; Shanmugam, Bharanidharan; Azam, Sami; Kannoorpatti, Krishnan
Abstract: Threats are potential events, intentional or not, that compromise the confidentiality, integrity, and/or availability of information systems. Defending against threats and attacks requires actionable threat intelligence. Using this intelligence to minimise risk, requires a systematic methodology or framework that recognises every possible threat scenario. This can be done with Threat Modelling (TM), which assists with identifying, understanding and providing visibility of threats affecting an organisation. The focus of this study is to determine TM limitations, strengths, and any perceivable gaps. It has also focused on identifying any possible enhancements that may improve TM performance and efficiency when modelling sophisticated attacks such as Advanced Persistent Threats (APT). Abstract : Advanced persistent threats; Threat modelling; Cyber threat model; Intelligence